Ten-year outcome of Eculizumab in kidney transplant recipients with atypical hemolytic uremic syndrome– a single center experience - Sam Kant; Anshul Bhalla; Sami Alasfar; Nada Alachkar (BMC Nephrology, 2020)
Abstract Background Atypical hemolytic uremic syndrome (aHUS) can result in severe kidney dysfunction, secondary to thrombotic microangiopathy. Eculizumab has been used to treat this disorder, and has resulted in favourable outcomes in both, native and transplanted kidneys. There is limited long term follow up data in kidney transplant recipients (KTRs) who received prevention and treatment with Eculizumab. We report our long term follow up data from our center to address safety and efficacy of this therapy in KTRs. Methods We performed a retrospective analysis of KTRs between January 2009 and December 2018. Clinical diagnosis of aHUS established with presence of thrombotic microangiopathy, acute kidney injury, absence of alternate identifiable etiology. We reviewed clinical data, including genetic testing for complement factor mutations, post-transplant course, and response to therapy including therapeutic and prophylactic use of eculizumab. Results Nineteen patients with aHUS received a total of 36 kidney transplants; 10 of them had 2 or more prior kidney transplants. Median age at time of last transplant was 37 years (range 27–59), 72% were female (n = 14), 78% Caucasian (n = 15), with 61% had live donor transplant (n = 12) as the last transplant. Eculizumab prophylaxis was given to 10/19 (56%) at the time of transplantation, with no aHUS recurrence during the follow up. Median duration of follow up was 46 (range 6–237) months. Mean estimated glomerular filtration rate (eGFR) at the time of last follow up was 59.5 ml/min/m2. No infections secondary to encapsulated organisms or other major infectious complications occurred during the follow up. Conclusions Eculizumab prophylaxis is safe and effective in KTRs with aHUS. Long term follow up demonstrates that it may be possible to discontinue prophylaxis carefully in selected patients with no evidence of complement mutations.